Direct Access to 5,6-Dihydropyrido[2′,1′:2,3]pyrido-Fused Imidazo [4,5-c]quinolines via Consecutive C–N and C–C Bond Formation in Deep Eutectic Solvent under Microwave Irradiation - Dasmahapatra, Upala; Choudhury, Badruzzaman; Ahmad, Md Gulzar; Maiti, Barnali; Chanda, Kaushik (Synthesis, 2025)
Deep eutectic solvents (DESs) are a novel class of ionic liquids that have recently gained considerable attention as a sustainable, nontoxic substitute for traditional organic solvents; recent years have seen an increasing demand for DES systems to synthesize various heterocyclic moieties. Polyheterocycle-containing scaffolds are important as potential therapeutic agents. Herein, we reported a tandem methodology for the synthesis of rarely explored 5,6-dihydropyrido[2′,1′:2,3]imidazo[4,5-c]quinolines and pyrido[2′,1′:2,3]imidazo[4,5-c]quinolines in a choline chloride based DES medium under microwave irradiation. This sustainable approach offers a clean, straightforward synthetic strategy under mild reaction conditions for the synthesis of a wide range these compounds in excellent yields.
Keywords: deep eutectic solvent; polyheterocycles; tandem; microwave irradiation